Antioxidant Defence of Dietary Squalene Supplementation on n-3 Poly Unsaturated Fatty Acids (PUFA)-Mediated Oxidative Stress in Young and Aged Rats - Obulesu, T; Asha, K K; Anandan, R; Mathew, S; Ganesan, B; Krishna, G; Lakra, W S (Fishery Technology, 2025)
Oxidative stress-induced aberrations in fatty acid composition of central nervous system during progression of aging are known to alter homeostatic processes of the whole organism. Antioxidants that accumulate in brain and neural tissue are potential candidates for prevention or treatment of disorders involving oxidative damage during disease progression. In the present study, an attempt was made to examine the antioxidant effect of squalene against n-3 polyunsaturated fatty acids (PUFA)-mediated oxidative stress in young and aged rats with respect to the changes in lipid peroxidation, enzymatic and non-enzymatic antioxidant status. Dietary co-intake of squalene significantly attenuated n-3 PUFA mediated oxidative stress in different regions of brain tissue of young and aged rats and maintained the cerebral antioxidant status at near normalcy. Though per se dietary supplementation of n-3 PUFA significantly elevated the enzymic and non-enzymic antioxidant levels in young rats, it diminished the antioxidant profiles in aged brain striatum, cortex and hippocampus regions. The results of the present study indicated that the combined dietary supplementation of squalene and n-3 PUFA might be a viable therapeutic strategy to ameliorate ageassociated oxidative stress in brain tissue.